Bailes da terceira idade : espaços de socialidade e consumo musical na cidade - Moreira, Juliana Segóvia (2015)
In the city, socialization spaces are destined to different kinds of public, which vary according to age, appreciation for music and socioeconomic level, based on belonging relations and several affinities between people, which reinforce the “being together to spend time”. The thematic approach of the research is focused on the universe of old people who frequent elderly`s dancing parties in Cuiabá (Mato Grosso, Brazil), their social practices and their music re-signification process, as consumption forms and subjectivity production. The more popular music is analyzed as a cultural product which allows the meaning production and the interaction between individuals when it is inscribed in a specific social and symbolic universe, permeating intersubjective circumscribed worlds in the city. Nine socialization spaces, classified as “bailões”, were identified in distinct neighbors – downtown and suburbs, varying between public and private spaces – allowing a mapping of a specific route of those who have the dancing parties as a relevant part of their daily life.